Myositis-specific autoantibodies in Japanese patients with juvenile idiopathic inflammatory myopathies. Issue 2 (4th March 2019) - Ueki, Masahiro; Kobayashi, Ichiro; Takezaki, Shunichiro; Tozawa, Yusuke; Okura, Yuka; Yamada, Masafumi; Kuwana, Masataka; Ariga, Tadashi
Abstract: Objectives: The aim of our study is to clarify the association of myositis-specific autoantibodies (MSAs) with clinical and laboratory features in Japanese patients with juvenile idiopathic inflammatory myopathies (JIIMs). Methods: We retrospectively analyzed the frequency of MSAs and their association with clinical or laboratory findings in 25 Japanese patients with JIIMs in Hokkaido district. Results: Eighteen of the 25 patients (72%) were positive for MSAs; seven with anti-melanoma differentiation associated gene (MDA) 5 (28%), five with anti-transcriptional intermediary factor (TIF)-1γ (20%), four with anti-MJ/nuclear matrix protein (NXP)-2 (16%), two with anti-Jo-1 (8%), one with anti- HMG-CoA reductase, one with anti-signal recognition peptide (SRP) antibodies (4% each), including co-existence and transition of MSAs in one patient each. Anti-MDA5 antibodies were related to interstitial lung disease (ILD) and arthritis but not to amyopathic juvenile dermatomyositis. Drug-free remission was achieved, once ILD was overcome in this group. Anti-TIF-1γ antibodies were associated with typical rashes and mild myositis. Anti-MJ/NXP2 and anti-SRP antibodies were associated with severe muscle weakness. No patient was complicated with malignancy. Conclusion: Anti-MDA5 antibodies are prevalent and closely associated with ILD in our series compared with other countries. There was no apparent difference in clinical features associated with other MSAs among races.